2003
DOI: 10.1103/physrevlett.90.188104
|View full text |Cite
|
Sign up to set email alerts
|

Electron Attachment to Uracil: Effective Destruction at Subexcitation Energies

Abstract: We demonstrate that electrons at energies below the threshold for electronic excitation (<3 eV) effectively decompose gas phase uracil generating a mobile hydrogen radical and the corresponding closed shell uracil fragment anion (U-H)(-). The reaction is energetically driven by the large electron affinity of the (U-H) radical. This observation has significant consequences for the molecular picture of radiation damage, i.e., genotoxic effects or damage of living cells due to the secondary component of high ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
293
5
18

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(340 citation statements)
references
References 33 publications
24
293
5
18
Order By: Relevance
“…6,7,12−14,37 Electron transmission spectroscopy and DEA studies have estimated the threshold energy for this channel to be at most 0.8 eV. 6,12 In our experiment, the analogous process could occur via…”
mentioning
confidence: 62%
“…6,7,12−14,37 Electron transmission spectroscopy and DEA studies have estimated the threshold energy for this channel to be at most 0.8 eV. 6,12 In our experiment, the analogous process could occur via…”
mentioning
confidence: 62%
“…Owing to resonance rearrangements in the electron system, the negative charge that might be expected to reside on N 1 after the H atom leaves is distributed widely over the molecule. This occurs more readily for this H atom than that on N 3 , and we attribute the low threshold for production of U-H ÿ H in uracil, reported by the calculations of Hanel et al [2] to be 0:8 0:1 eV, to this cause. In fact, the threshold may be as low as 0.6 eV, if these authors have ignored the change in zero point energy.…”
mentioning
confidence: 84%
“…This work, in part, has served to motivate further gas phase studies of electron collisions with the DNA bases, the RNA base uracil, and the halouracils in an effort to understand the fundamental mechanisms involved. Most recently, Hanel et al [2] (uracil), Denifl et al [3] (uracil, thymine and cytosine), Abouaf et al [4] (thymine and 5-bromouracil), and Denifl et al [5] (5-chlorouracil) have examined the electron energy dependence of the production of various anion fragments and made estimates of the magnitudes of the dissociative electron attachment (DEA) cross sections. The radiological significance of the halouracils has been discussed in several of these references and will not be repeated here.…”
mentioning
confidence: 99%
“…Gas phase experiments [43,46,47,48,49,50,51,52] revealed that below the electronic excitation energy level (3-4 eV), the TNI that are most likely to form are shape resonances of the basic subunits of DNA. At higher energies the TNI formed are Feshbach resonances.…”
Section: Dna Damage By Low-energy Electronsmentioning
confidence: 99%